Inflation in Bangladesh : Trends, Sources and Policy Options - World Bank (Washington, DC, 2013)
Inflation in Bangladesh has increased from 1.9 percent in FY01 to 7.2 percent in FY06. The biggest increase was in food prices. Food price inflation increased from 1.4 percent in FY01 to 7.8 percent in FY06. By contrast, non-food price inflation only doubled during the same period. Food price inflation has been well above non-food inflation since FY04. The rise in food inflation could have resulted from developments in global commodity markets, particularly since FY05, increases in domestic production costs, and domestic demand. Inflation increased in most major world economies during FY06 following a surge in international commodity, energy and related fuel prices. The relationship between inflation and growth remains controversial both in theory and in empirics. The inflation-growth relationship for Bangladesh, India, Pakistan and Sri Lanka none of these countries have had high inflation episodes in recent decades. Their analysis shows that growth rates and inflation rates for all four countries are co integrated, implying that there is a long run relationship between inflation and growth in all four countries.